The messingkauf dialogues - Brecht, Bertolt 1898-1956; Willett, John (London Methuen, 2002)
The Messingkauf dialogues are the longest but in some ways the most light hearted of all Brecht's discussions of theatre. Here Actor, Actress, Dramaturg (or literary adviser) and Electrician argue with the Brechtian Philosopher who wants to exploit their talent for his own purposes. The result is a lively debate about the place of art in society.